Motivated Beliefs and the Elderly's Compliance With Covid-19 Measures - Ferdinand von Siemens (Center for Economic Studies and Ifo Institute (CESifo), 2021)
Although the elderly are more vulnerable to COVID-19, the empirical evidence suggests that they do not behave more cautiously in the pandemic than younger individuals. This theoretical model argues that some individuals might not comply with the COVID-19 measures to reassure themselves that they are not vulnerable, and that the incentives for such self-signaling can be stronger for the elderly. The results suggest that communication strategies emphasizing the dangers of COVID-19 could backfire and reduce compliance among the elderly.
Keywords: C70; D91; D82; I12; I18; 330; motivated beliefs; compliance behaviour; age; health; Covid-19